2016
DOI: 10.1123/jpah.2015-0482
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Surveillance of Physical Activity Habits of Latinas Enrolled in a 12-Month Physical Activity Intervention

Abstract: Background Long-term physical activity surveillance has not been conducted among Latinas. This study explored the variability of daily physical activity habits of inactive adult Latinas participating in a 12-month physical activity intervention. Methods We collected objective physical activity data (pedometer) from 139 Spanish speaking Latinas (age = 41.6 ± 10.1 years; BMI = 29.6 ± 4.3 kg/m2) enrolled in a 12-month physical activity intervention. Total and aerobic steps (>100 steps/minute) were computed by y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…We observed a decrease in physical activity on Sunday compared to weekdays in both the high and low depressive symptom groups. Lower physical activity, objectively measured, mainly in the weekend has been observed in previous work 21,22,36 . One study using objectively measured step counts found that participants with mild to severe depressive symptoms walked less that those with low depressive symptoms overall, and that for both groups physical activity declined in the weekend 28 .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We observed a decrease in physical activity on Sunday compared to weekdays in both the high and low depressive symptom groups. Lower physical activity, objectively measured, mainly in the weekend has been observed in previous work 21,22,36 . One study using objectively measured step counts found that participants with mild to severe depressive symptoms walked less that those with low depressive symptoms overall, and that for both groups physical activity declined in the weekend 28 .…”
Section: Discussionsupporting
confidence: 74%
“…Further, in urban adults in the United Kingdom, physical activity was lower on Sundays compared to weekdays and Saturdays 21 based on accelerometer data. In a 12-month study with Latina women using pedometers during a physical activity intervention, physical activity was higher on weekdays 22 . By contrast, one study in older adults using a body-xed sensor to measure physical activity for seven days found no differences between weekend and weekday physical activity 23 .…”
Section: Introductionmentioning
confidence: 99%
“…These data extend research with the population of mature [16,27] and elderly [10,17]. Equality of the number of steps of general physical activity in summer to the average year is consistent with the data of the research of the elderly [18].…”
Section: Discussionsupporting
confidence: 73%
“…It was established that during the year (pedometers) PA in people of mature age in summer was greater than in winter. The number of steps was 6509, 20 % of them are aerobic steps (more than 100 steps per minute) [16]. In the group of adults with normal body mass index (BMI), there was a decrease in the number of steps in winter compared to summer [17].…”
Section: Introductionmentioning
confidence: 99%
“…It may be that self-assessed PA measures are not capturing the right type of activities, particularly in marginalized populations with limited resources to be active. For example, there is some evidence to suggest that Hispanic subgroups, like immigrants, may be more likely to walk for utilitarian purposes, but less likely to engage in recreational PA [59] and that duration in the United States has a negative relationship with the amount of walking Hispanic groups engage in [60]. Self-reported instruments, like the CHAMPS may still provide better insight into what types of activities people engage in in general, but may need to be modified to include race/ethnic or rural/urban specific types of preferred activities in order to get a better sense of actual PA and to effectively evaluate the success of intervention programs [61].…”
Section: Discussionmentioning
confidence: 99%